2017
DOI: 10.1073/pnas.1613844114
|View full text |Cite
|
Sign up to set email alerts
|

Parietal neurons encode expected gains in instrumental information

Abstract: In natural behavior, animals have access to multiple sources of information, but only a few of these sources are relevant for learning and actions. Beyond choosing an appropriate action, making good decisions entails the ability to choose the relevant information, but fundamental questions remain about the brain's information sampling policies. Recent studies described the neural correlates of seeking information about a reward, but it remains unknown whether, and how, neurons encode choices of instrumental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 61 publications
(71 reference statements)
7
62
0
Order By: Relevance
“…Using functional magnetic resonance imaging (fMRI) we examined which brain areas were modulated by outcome uncertainty and expected value upon lottery presentation, and their updates upon outcome presentation. We hypothesized that during lottery presentation, brain regions associated with uncertainty or risk, such as insular cortex (Critchley et al, 2001;Jepma et al, 2012;Paulus et al, 2003;Preuschoff et al, 2006Preuschoff et al, , 2008 and parietal cortex (Foley et al, 2017;Huettel et al, 2005), would be modulated by outcome uncertainty. During outcome presentation, we expected increased activity in brain regions involved in curiosity relief and information updating, such as the insula (Jepma et al, 2012;Preuschoff et al, 2008), orbitofrontal cortex (Blanchard et al, 2015;Jepma et al, 2012) and ventral striatum (Jepma et al, 2012;Wittmann et al, 2008).…”
mentioning
confidence: 99%
“…Using functional magnetic resonance imaging (fMRI) we examined which brain areas were modulated by outcome uncertainty and expected value upon lottery presentation, and their updates upon outcome presentation. We hypothesized that during lottery presentation, brain regions associated with uncertainty or risk, such as insular cortex (Critchley et al, 2001;Jepma et al, 2012;Paulus et al, 2003;Preuschoff et al, 2006Preuschoff et al, , 2008 and parietal cortex (Foley et al, 2017;Huettel et al, 2005), would be modulated by outcome uncertainty. During outcome presentation, we expected increased activity in brain regions involved in curiosity relief and information updating, such as the insula (Jepma et al, 2012;Preuschoff et al, 2008), orbitofrontal cortex (Blanchard et al, 2015;Jepma et al, 2012) and ventral striatum (Jepma et al, 2012;Wittmann et al, 2008).…”
mentioning
confidence: 99%
“…This so-called information-prediction-error signal is presumed to arise from the value of information, 9-11, 18, 79 and has been reported in the same midbrain dopaminergic regions as standard reward prediction errors, 9,10 implying that the two signals might be strongly related. 84 Indeed, our model accounts for information prediction errors as a side effect of anticipation-dependent reward predictions, which we show correlates with BOLD signal in dopaminergic midbrain regions 9,10 as well as in the mPPC 36 (see also 110 ).…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, the model's signal correlated significantly with BOLD in a midbrain dopaminergic region encompassing the ventral tegmental area and substantia nigra (VTA/SN) ( Figure 3A; p < 0.05, small volume FWE correction; 48 [4, −26, 20], t = 3.78). We also found that BOLD in the medial posterior parietal cortex (mPPC) 36,110 correlated significantly with the model's predicted signal ( Figure 3A; p < 0.05, cluster-level whole brain FWE correction with the height threshold , but not with a simpler, so-called state prediction error signal (1−p reward when reward predictive cue was presented, |0 − p reward | when no-reward predictive cue was presented). The differences between the average regression coefficients in the mPPC and in the VTA/SN were significant in the mPPC (p < 0.001, a standard permutation test in which we permuted the average regression coefficients), and the VTA/SN (p < 0.001 permutation test).…”
Section: The Dopaminergic Midbrain Encodes Anticipation-dependent Rewmentioning
confidence: 84%
“…It remains unknown whether this network could also motivate seeking of other types of information, such as information about instrumental contingencies (i.e. what action will be required to gain the reward 60 ). In natural environments these types of information are likely to synergize with each other: if an agent has a subjective preference to resolve uncertainty in order to better predict future rewards, then the agent will likely be better at learning the objective value of resolving that uncertainty to better take actions and control rewards.…”
Section: A Neural Network For Information Seekingmentioning
confidence: 99%